2017
DOI: 10.1089/end.2016.0569
|View full text |Cite
|
Sign up to set email alerts
|

C-SATS: Assessing Surgical Skills Among Urology Residency Applicants

Abstract: Crowd-source assessment of resident applicant surgical skills has good inter-rater agreement with expert physician raters but not with a computer-based objective motion metrics software assessment. Overall applicant rank was affected to some degree by the crowd performance rating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 19 publications
(35 reference statements)
0
33
1
Order By: Relevance
“…Notably, evidence supports its ability to discriminate amongst staff surgeons of differing case volume [16], as well as across a single surgeon's learning curve [13]. The vast majority of literature using the GEARS score has found it to be a reliable assessment method [4,11,16,24,25,27,28]. However, a study of robotic renal hilar dissection using oriented expert raters showing poor internal consistency [17], and Hung et al [21] found that while trainee self-assessments and faculty evaluations correlated weakly, inter-faculty reliability was better when assessing residents [intraclass correlation (ICC) = 0.77] and fellows (ICC = 0.45).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Notably, evidence supports its ability to discriminate amongst staff surgeons of differing case volume [16], as well as across a single surgeon's learning curve [13]. The vast majority of literature using the GEARS score has found it to be a reliable assessment method [4,11,16,24,25,27,28]. However, a study of robotic renal hilar dissection using oriented expert raters showing poor internal consistency [17], and Hung et al [21] found that while trainee self-assessments and faculty evaluations correlated weakly, inter-faculty reliability was better when assessing residents [intraclass correlation (ICC) = 0.77] and fellows (ICC = 0.45).…”
Section: Resultsmentioning
confidence: 96%
“…The Global Evaluative Assessment of Robotic Skills (GEARS) tool, developed by Goh et al. , has been applied to urological assessments on multiple occasions , and has the strongest validity argument supporting its use in the assessment of robotic skill. Its generic framework has allowed it to become a widely accepted method of assessment across multiple procedures and even across specialties .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations